(untitled) (REMUNOM, 2025)
Burnout is a syndrome of exhaustion that may emerge as a response to chronic occupational stress. These feelings of exhaustion can also be associated with academic demands, increasing mental detachment from studies and a sense of fatigue related to studying or working. Individuals who perform multiple societal roles—such as working and studying—while also managing social life commitments are more prone to experiencing symptoms of mental stress. This study aimed to identify the prevalence rate of Burnout Syndrome and its triggering factors by investigating the sociodemographic profile of nursing students at a university in northern Tocantins, Brazil. This is an exploratory study, quali-quantitative research study that began with a literature review on the subject. A questionnaire addressing exhaustion, depersonalization, demotivation, and daily life was used as the primary data collection instrument. The results revealed a high prevalence of the syndrome among students at the institution under study.